(untitled) - Banks, William J. (Baltimore, 1981)
Applied Veterinary Histology gives excellent information on the basic tissues and the organs and organ systems they comprise. It has excellent diagrams and pictures, but no color(except the tissue slide section in the begining). I am a freshman vet student a Mississippi State University and this is one of my most frequently consulted resources
Keywords: Veterinary histology,Anatomy, Veterinary,Histology